Phase 1 Safety, Pharmacokinetics, and Fluorescence Imaging Study of Tozuleristide (BLZ-100) in Adults With Newly Diagnosed or Recurrent Gliomas. Issue 4 (9th May 2019) - Patil, Chirag G; Walker, David G; Miller, Dennis M; Butte, Pramod; Morrison, Beth; Kittle, David S; Hansen, Stacey J; Nufer, Kaitlin L; Byrnes-Blake, Kelly A; Yamada, Miko; Lin, Lynlee L; Pham, Kim; et al.
Abstract: BACKGROUND: Fluorescence-guided surgery (FGS) can improve extent of resection in gliomas. Tozuleristide (BLZ-100), a near-infrared imaging agent composed of the peptide chlorotoxin and a near-infrared fluorophore indocyanine green, is a candidate molecule for FGS of glioma and other tumor types. OBJECTIVE: To perform a phase 1 dose-escalation study to characterize the safety, pharmacokinetics, and fluorescence imaging of tozuleristide in adults with suspected glioma. METHODS: Patients received a single intravenous dose of tozuleristide 3 to 29 h before surgery. Fluorescence images of tumor and cavity in Situ before and after resection and of excised tissue ex Vivo were acquired, along with safety and pharmacokinetic measures. RESULTS: A total of 17 subjects received doses between 3 and 30 mg. No dose-limiting toxicity was observed, and no reported adverse events were considered related to tozuleristide. At doses of 9 mg and above, the terminal serum half-life for tozuleristide was approximately 30 min. Fluorescence signal was detected in both high- and low-grade glial tumors, with high-grade tumors generally showing greater fluorescence intensity compared to lower grade tumors. In high-grade tumors, signal intensity increased with increased dose levels of tozuleristide, regardless of the time of dosing relative to surgery. CONCLUSION: These results support the safety of tozuleristide at doses up to 30 mg and suggest that tozuleristide imaging may be useful for FGS of gliomas. Graphical Abstract: